Acantholippia seriphioides : chemical biodiversity of wild populations from the Cuyo Region in Argentina = Acantholippia seriphioides: Biodiversidad química de poblaciones silvestres de la región de Cuyo de la Argentina - van Baren, Catalina María (2015)
Nineteen samples from the aerial parts in bloom of Acantholippia seriphioides (Verbenaceae) were collected in three provinces belonging to the Cuyo region of Argentina. The essential oils were obtained by hydrodistillation, yielding between 0.57 and 2.46% (v/w). On the basis of the 13 main compounds determined by GC-FID-MS, representing the 87.2 and 95.3% of the total identified, four chemotypes were determined: carvacrol, thymol, cis and trans-dihydrocarvone and linalool-geraniol. The co-occurrence of different chemotypes in a same population indicates that the sample collection must be carefully done with the aid of an in situ olfactory testing of the plants, since no morphological differences at first sight were observed among them. The results showed in this study suggest that the pattern of variations for this species exists throughout its natural distribution area.